Pitfalls in the identification of Enterococcus species and the detection of vanA and vanB genes. (5th August 2016) - Papadimitriou‐Olivgeris, M.; Filippidou, S.; Kolonitsiou, F.; Drougka, E.; Koutsileou, K.; Fligou, F.; Dodou, V.; Sarrou, S.; Marangos, M.; Vantarakis, A.; Anastassiou, E.D.; Petinaki, E.; et al.
Abstract: The aims were to assess the performance of Vitek 2 in identifying enterococcal species and the implementation of GeneXpert ® vanA/vanB PCR for the detection of vancomycin‐resistant enterococci (VRE). Gram‐positive cocci from clinical and environmental specimens ( n  = 431) suspicious of being enterococci by conventional methods were evaluated by Vitek 2. This system identified 296 Enterococcus faecium, 87 Enterococcus faecalis, 10 Enterococcus villorum, 9 Enterococcus gallinarum, 9 Enterococcus durans, 5 Enterococcus casseliflavus, 1 Enterococcus spp. and 14 isolates as Non‐ Enterococcus . All strains were submitted to pulsed field gel electrophoresis (PFGE) analysis showing 64 banding patterns. Representative strains from each banding pattern were further characterized to species level by 16S rDNA sequencing. The misidentification rate by Vitek 2 to species level among 429 molecularly identified enterococci was 6% (26 isolates). Additionally, 372 rectal swabs were obtained from critically ill patients. They were evaluated for the presence of VRE by ChromID VRE combined with in‐house PCR vs GeneXpert ® . GeneXpert ® showed high (>92%) sensitivity, specificity, accuracy for vanA ‐positive Enterococcus detection, as well as, sensitivity and specificity for vanB ‐positive strains. Positive predictive value for detection of vanB ‐positive enterococci by GeneXpert ® vanA / vanB was low (30%). GeneXpert ® showed the same efficacy as ChromID VRE in detecting vanA ‐positive enterococci, but lower for vanB ‐gene detection. Significance and Impact of the Study: The study shows that even though the performance of Vitek 2 Advanced Expert System was good in identifying enterococci to species level, it is important to verify results by a molecular method when phenotypic findings are discordant with epidemiologic patterns. Furthermore, GeneXpert ® vanA / vanB PCR and ChromID VRE combined with in‐house PCR were applied in rectal samples for the detection of VRE colonization among critically ill patients. GeneXpert ® showed an excellent performance in detecting vanA ‐positive enterococci, but false‐positive results for vanB ‐gene detection render its application problematic in departments with high incidence of vanB ‐positive enterococci. Abstract : Significance and Impact of the Study: The study shows that even though the performance of Vitek 2 Advanced Expert System was good in identifying enterococci to species level, it is important to verify results by a molecular method when phenotypic findings are discordant with epidemiologic patterns. Furthermore, GeneXpert ® vanA / vanB PCR and ChromID VRE combined with in‐house PCR were applied in rectal samples for the detection of VRE colonization among critically ill patients. GeneXpert ® showed an excellent performance in detecting vanA ‐positive enterococci, but false‐positive results for vanB ‐gene detection render its application problematic in departments with high incidence of vanB ‐positive enterococci.